Impact of Hyperthyroidism on Biochemical Markers of Bone Metabolism - Sarah Hashim Mhaibes; Inaam Ahmed Ameen; Eman Saadi Saleh; Kaled Nather Taha; Hawaa Salman Kamil (Journal of Clinical and Diagnostic Research, 2019)
Introduction: Hyperthyroidism is a common endocrine disorder associated with multi-systemic effects, a rarely reported of which is bone loss in newly diagnosed hyperthyroid cases. Elevated thyroid hormones directly stimulate bone cells and accelerate bone turnover. Increased serum Osteocalcin (OSC) levels can be used as a bone biomarker in hyperthyroidism disorder. Aim: To elucidate the effect of excess thyroid hormone on the serum OSC, alkaline phosphatase, calcium and phosphorus levels in newly diagnosed hyperthyroidism patients. Materials and Methods: The study was conducted at the National Center of Teaching Laboratories of Medical City Institute, Baghdad, Iraq. Newly diagnosed 50 patients with hyperthyroidism (19 males, 31 females), and 30 age and sexmatched healthy controls (9 males, 21 females) were included in the study. The detailed history of the participants were recorded and thyroid profile including Thyroid Stimulating Hormone (TSH), Total tri-iodothyronine (T3 ) and Total tetra-iodothyronine (T4 ) levels, and biochemical markers of bone metabolism-serum OSC, Alkaline Phosphatase (ALP), calcium and phosphorus were analysed. Normality was calculated using Shapiro-Wilk test. Mann-Whitney test was used to determine association among non-parametric data. Independent t-test was used to compare the difference between age groups. Receiver Operating Characteristic curve (ROC curve) was used to identify the validity of markers as an indicator of infection, and the markers were compared according to the area under the curve. Results: In hyperthyroidism patients, the serum total T4 levels, and T3 levels were significantly elevated (p-value <0.0001), while TSH (p-value <0.0001) were lowered as compared to the control group. Significant difference was observed in serum levels of OSC (p-value <0.0001), ALP (p-value <0.0001) and calcium (p-value=0.0004) levels in hyperthyroidism patients and control group, while no significant (p-value=0.17) difference was observed in serum phosphorus levels. Elevated serum OSC, ALP and calcium were significantly associated with the elevated thyroid hormones (total T3 and total T4 ). Conclusion: Association of elevated OSC, ALP and calcium levels with elevated levels of thyroid hormones in hyperthyroid patients indicates that hyperthyroidism influences the bone mineral homeostasis. OSC serves as a better biomarker than the ALP in the risk assessment of bone loss in newly diagnosed hyperthyroidism patients.